Budgetary Participation, Compensation, and Performance of Local Government Working Unit: The Intervening Role of Organizational Commitment - Afrizal Tahar; Hafiez Sofyani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2020)
Research aims: This study aims to examine the influence of budgetary participation and compensation influence toward local government performance with organizational commitment as an intervening.Design/Methodology/Approach: The sample used was government officials in Magelang City, Indonesia. The respondents involved in this study were head of the division, head of the sector, head of sub-division, head of sub-sector, and staff. This research used a purposive sampling method. The type of data is primary data that were collected by distributing the questionnaires. 116 respondents were involved as the sample. Partial Leas Square (PLS) was employed to test the hypotheses.Research findings: This study revealed that budgetary participation and compensation influenced organizational commitment. Also, it showed that budgetary participation and compensation indirectly influenced on local government performance through organizational commitment.Theoretical contribution/Originality: This study gives evidence that organizational commitment has a role as a full intervening variable on the relationship between budgetary participation and compensation toward performance.Practitioner/Policy implication: This study gives beneficial information to the regulator and local government management to enhance agencies’ performance.Research limitation/Implication: This study only conducted in Magelang City. Arguably, the reader needs to be carry full in reading this study result, mainly to generalize the study results.